The gene expression and protein profiles of ADAMTS and TIMP in human chondrosarcoma cell lines induced by insulin: The potential mechanisms for skeletal and articular abnormalities in diabetes. Issue 1 (February 2020) - Akyol, Sumeyya; ,; Karagoz, Zehra; Inan, Nuran Dingil; Butun, Ilknur; Benli, Ismail; Demircan, Kadir; Yigitoglu, Muhammet Ramazan; Akyol, Omer; ,; Sahin, Semsettin; Ozyurt, Huseyin
No abstract available